Shakespeare in parts - Palfrey, Simon (Oxford University Press, 2007)
Shakespeare's drama originally circulated in the form of the individual actor's part, containing only a single character's speeches and brief cues. This collaboration of original theatre history with exciting literary criticism captures anew Shakespeare's development as a writer.